'Fate Leads the Willing, and Drags the Unwilling': Eric Werner, Wissenschaft des Judenthums, and the Postwar Reconstruction of Jewish Music Study. Issue 1 (1st March 2021) - Cohen, Judah M.
Abstract: In this article, I explore the role that Austrian-born musicologist/composer Eric Werner (1901–1988) cultivated as a representative of musical Wissenschaft des Judenthums in postwar America. I focus here on the diary that Werner kept between 1955 and 1957 – a heretofore untapped resource – which chronicles his efforts to build intellectual refugee networks while simultaneously helping to restart an international network of Jewish music discourse spanning America, Europe and Israel. Music, in Werner's view, required a scientific basis for study from which authentic practices could be rebuilt. Thus, while Werner relied on revitalising cantors as vessels of Jewish music, he viewed musicology as the core discipline from which Jewish music 'tradition' could arise.